A relevância da participação da vítima na justiça penal consensual - Morais, Gabriela Reston Pinto (2023)
The Brazilian criminal justice is considered by most of the modern society as a slow system, extremely bureaucratic and based on impunity. At the same time, the criminality is getting more organized, complex, and well structured, in a way that, in order to satisfy the social expectations and recover the criminal justice credibility in the country, it’s necessary to rethink the traditional model. It is in this context that the consensus criminal justice system emerges, nationally and internationally, so that the consensus methods pursue the application of an effective justice, faster, based on rationalization and efficiency, not excluding the fundamental rights and guarantees, but making them more flexible in order to please all people involved in the criminal conflict, especially the victim, that shows off as such an essential participant. Therefore, the goal of this work is to approach the victim’s role in the consensus criminal justice system, so that it is possible to analyze if there is or there is not an effective participation of the victim in the Brazilian consensual criminal procedure, considering the Brazilian consensus institutes, such as the ones established on the Law nº 9.099/95, the Restorative Justice and the Non-criminal Prosecution Agreement. In the research, based on the deductive method, the qualitative methodology has been used, drawing on articles, multiple doctrines, legislation and jurisprudence. It proposes to show the relevance of the victim’s role in the Brazilian consensual criminal justice, so that to verify that victim’s participation, a right that is guaranteed inside and outside the Brazilian nation is, in fact, applied and exercised by the offended, as well as the importance of this participation